2002
DOI: 10.1093/qjmed/95.11.733
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose folic acid lowers plasma homocysteine levels in women of child-bearing age

Abstract: In this sub-population, low doses of folic acid significantly lower plasma homocysteine. This could be achieved safely by fortification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…Mean concentrations of tHcy in the present study were similar [ 47 , 48 ] or lower than others in young women [ 49 ] or in a random population sample [ 50 ]. Small doses of folate have been shown to reduce tHcy in a young population [ 49 ] so the high blood folate levels observed in the present study may be protective of hyperhomocysteinaemia, which was found in 2% of women in this study, half of that in previous reports in young women [ 51 ].…”
Section: Discussionsupporting
confidence: 75%
“…Mean concentrations of tHcy in the present study were similar [ 47 , 48 ] or lower than others in young women [ 49 ] or in a random population sample [ 50 ]. Small doses of folate have been shown to reduce tHcy in a young population [ 49 ] so the high blood folate levels observed in the present study may be protective of hyperhomocysteinaemia, which was found in 2% of women in this study, half of that in previous reports in young women [ 51 ].…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have investigated the dose-response relationship of folic acid with tHcy in the lowdose range, using either capsules or fortified breakfast cereals. [40][41][42][43] All studies were conducted in populations in which there was no folic acid fortification. These studies indicate that a supplement should contain at least 400 mg/day for maximal tHcy lowering.…”
Section: Folatementioning
confidence: 99%
“…This possibility is consistent with the hypothesis that B-vitamins inadequacy per se is a major causal pathway to cognitive decline. Other studies found that doses in the range of 0.2-0.5 mg/day achieve maximum reduction in tHcy levels in healthy populations and that a higher dose of 0.8 mg/day is required for maximal lowering of tHcy in individuals with vascular diseases [52][53][54]. There are several ways by which this could be accomplished: one is by comparing responders to nonresponders within the treatment arm and by analyzing the extent of response to treatment by baseline B-vitamin status and change.…”
mentioning
confidence: 99%
“…In the Framingham heart study, it was shown that the inverse association between plasma tHcy and folate intake plateaus when folate intake exceeds 0.4 mg/day [51]. Other studies found that doses in the range of 0.2-0.5 mg/day achieve maximum reduction in tHcy levels in healthy populations and that a higher dose of 0.8 mg/day is required for maximal lowering of tHcy in individuals with vascular diseases [52][53][54]. Hence, increasing folate intake over 0.8 mg/day would not be expected to have additional benefit and may in fact diminish efficacy.…”
mentioning
confidence: 99%